Proposta de melhorias no gerenciamento de resíduos sólidos em uma indústria de papel e celulose a partir da aplicação da metodologia PDCA (Plan, Do, Check, Act) - Queiroz, Hellen Carolina Nunes (Universidade Federal de São Carlos, 2023)
The population is susceptible to several environmental problems that affect it, among them are problems related to the management of solid waste. In 2015, the UN defined 17 SDGs (Sustainable Development Goals) that are part of the so-called “Agenda 2030”, which deals with a global pact signed at the United Nations Summit by 193 countries. The 17 objectives break down into 169 goals aimed at overcoming the challenges of sustainable development in the world, in order to promote sustainable global growth by the year 2030. Among the established goals, the company, where the study will be carried out, adopted the goal of “Landfill Zero” which aims not to send any type of waste to landfills by 2030. The pulp and paper industry is a major generator of solid waste of various types and classes, waste that needs management and final disposal. Some of the waste generated in the industry is already destined for purposes other than landfills, such as incineration, recycling, re-refining, energy use, etc., but there are still opportunities that can and will be explored throughout this work. With that in mind, the need arose to apply improvements regarding issues related to solid waste from the factory, in order to have a more organized, safe and efficient management, so throughout this project, the PDCA methodology was applied to identify the main gaps regarding to waste management and improvements were proposed, mostly focused on internal operating procedures and applications of improvements in waste storage locations within the factory, based on process flow updates and improving the company's internal indicators aimed at organization.
Proposal for improvements in solid waste management in a paper and pulp industry from the application of the PDCA (PLAN, Check, ACT) methodology
Keywords: Resíduos Sólidos; ODS (Objetivos de Desenvolvimento Sustentável); Melhorias; Meio Ambiente; Indústria; Solid Waste; SGD (Sustainable Development Goals); Improvements; Environment; Industry; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS